Pengaruh gender, gaya kepemimpinan, dan budaya organisasi terhadap kinerja karyawan (Studi kasus pada PT XYZ) - Soelistyoningrum, Jenia Nur (Universitas Tarumanagara, 2017)
The purpose of this empirical study is to analyze the effect of gender, leadership style, and organizational culture on the performance of employees. The research samples consist of 80 respondents. This research uses primary data obtained by distributing questionnaires to PT XYZ employees who meet the criteria that have been determined through purposive sampling. This research uses multiple linear regression analysis. The results show that gender, leadership style, and organizational culture positively influence the performance of employees.